DAMPAK BIMBINGAN ONLINE DAN LATIHAN MEDITASI VIPASSANA TERHADAP KESEHATAN MENTAL - Nur Amim; Thjia Khie Khiong; Partono Partono (AGUSPATI Research Institute, 2023)
Corona virus is a virus that attacks especially in the respiratory tract caused by a type of virus that is a relative of Sars (SARS-CoV-2. The rate of spread of Covid-19 in Indonesia is relatively fast, so this situation also has a major impact on teaching and learning activities which require a social distancing system. Religious activities have also been affected by the pandemic, especially prayer activities which are usually routinely carried out by Buddhists, pre-pandemic temple activities which were face-to-face, whereas during the pandemic there was a change in learning and teaching procedures, namely by utilizing distance learning facilities or known as the online system. (on the network). Many people experience mental health problems, especially during the pandemic. Mental health means the health of all aspects of development which include the physical and psychological. The total population in this study was less than 100, so all members of the population were used as samples. Data analysis is used to answer research problems that have been formulated, because the data to be collected is in the form of numbers, the data processing technique used is statistics. The data collected will be analyzed using the linear regression formula with the help of computer statistical Package for Social Sciences (SPSS 21) software for windows. The purpose of this study is to find out how much influence online guidance and vipassana meditation practice have on the mental health of KDAB Pariyapunati Indonesia Batch 24 participants in 2023. The results of this study can be concluded that there is online guidance and vipassana meditation practice on the mental health of KDAB Pariyapunati Indonesia batch 24 participants in 2023, namely with a regression coefficient value of 8.25 which shows a strong relationship between the variables of online guidance and vipassana meditation practice on changes in mental health , and shows a coefficient of determination of 0.681, thus meaning that 68.0% of the mental health of KDAB Pariyapunati Indonesia batch 24 participants in 2023 is influenced by online guidance and vipassana meditation practice while the other 32.0% is influenced by other factors not included in the the regression. These factors are the family environment, social environment, peers, and modeling.